RELATIONSHIP BETWEEN THE PARENT'S SOCIAL ECONOMIC STATUS AND STUDENT LEARNING ENVIRONMENT WITH MATHEMATICAL LEARNING ACHIEVEMENTS IN SMP N 3 WATES - Arief Wibowo; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Â This study aims to analyze the relationship between parents' socioeconomic status and the learning environment of students with mathematics learning achievement for students of class VIII in the second semester of SMP N 3 Wates Kulon Progo in the 2014/2015 academic year. The population in this study were all students of class VIII Semester II as many as 75 students, consisting of 3 classes and each class consisting of 25 students. Data collection techniques used by the test method to obtain data on mathematics learning achievement, questionnaire method to obtain data on the socioeconomic status of parents and student learning environment. Item analysis uses the validity test and the reliability test. Hypothesis testing using product-moment correlation analysis and multiple linear regression analysis. The results showed that parents' socioeconomic status had a positive and significant effect on mathematics learning achievement with simple correlation analysis and the t-test obtained a correlation coefficient of 0.959. The student learning environment has a positive and significant effect on mathematics learning achievement, with simple correlation analysis and t-test obtained correlation coefficients of 0.987. Parents' socioeconomic status and student learning environment have a positive and significant effect on mathematics learning achievement obtained by the double determinant coefficient of 0.974, multiple linear regression equations Y = -0.000205X1+0.898505X2 â€“ 26.981980, this shows that the socioeconomic status of parents and learning environment towards mathematics learning achievement is 97.4%. In the calculation obtained relative contributions from the socioeconomic status of parents by 0.03776% and from the student learning environment by 99.96224. An effective contribution can be obtained from the parents' socioeconomic status by 0.03677% and from the student learning environment by 97.334112%.